Forecasting the prospects for the accession of the Republic of Uzbekistan to the Eurasian Economic Union - Kh.R.Nuriddinova; S.A.Kamalov; M.Zh.Khalimov (Genius Journals, 2022)
Today, the Republic of Uzbekistan is negotiating cooperation with the Eurasian Economic Union (EAEU). The steps taken make us think about the feasibility of such decisions within the framework of the economic situation in the country. In addition,the factors influencing the decision-making regarding accession to the EAEU have been analyzed
Keywords: Republic of Uzbekistan; Eurasian Economic Union; WorldTrade Organization; forecasting tube